(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The aim of the experiment was to determine the biomass yield, morphological characteristics and nutritive value of different high yielding Napier cultivars according their cutting intervals. This study mainly discussed about four Napier cultivars named BLRI-Napier-4, Wruk-Wona, Napier-Hybrid (Japan) and MarkEron. The cutting interval was 45 days. The result showed significant difference (p<0.05) in 3rd cutting into these three cutting in case for biomass yield, number of hill, number of tiller and plant height. The stem and leaf ratio was higher in 2nd cutting in BLRI-Napier-4. For botanical fraction, leaf contained more dry matter than stem. Crude protein was higher in leaf portion for different Napier cultivars. As considering the cutting interval, the 3rd cutting contained higher dry matter compare to other cut. MarkEron cultivar showed more significant difference (p<0.001) for Ash and CP content into its three cutting. High level of oxalate found in BLRI-Napier-4. Considering biomass yield, BLRI-N-Hybrid was the higher value. Crude protein was higher in MarkEron cultivar. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 100-107